Educational policy borrowing in a globalized world. Issue 1 (5th May 2015) - Van Huy, Nguyen; Hamid, M. Obaidul
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to shed light on the process of adopting and accommodating a global language education framework, namely the Common European Framework of Reference (CEFR) for languages, in the context of Vietnam. Design/methodology/approach – The data to develop the argument of the paper are obtained from a doctoral research project that aims to understand the reception, interpretations and responses of key stakeholders in the process of enacting the CEFR in a Vietnam public university. The study was designed as a qualitative case study with data being collected using policy document analysis, classroom observation and in-depth interviews with 21 purposively sampled participants, including school administrators, English language teachers and students over a period of six months. Findings – The paper argues that the adoption of the CEFR, as it currently stands, can be seen at best as a "quick-fix" (Steiner-Khamsi, 2004, p. 58) solution to the complex and time-consuming problem of improving the quality of English language education in Vietnam, which fails to address some critical issues in the practice of teaching and learning the language in the country. Originality/value – The study speaks to the body of literature on the CEFR as a contemporary global language policy borrowing phenomenon in developing countries. It contributes to a better understanding of how a global language policy is adopted and appropriated at the grass-root level.